HYDRAULIC ASPECTS OF LOGJAM FORMATION DURING EXTREME HIGH FLOODS - Andrey P. Lepikhin; Anna A. Wozniak (Водное хозяйство России: проблемы, технологии, управление)
The article discusses the mechanisms of formation of congestion of trees in front of the bridge during high floods that can significantly increase the water level in the pre-bridge zone. The analysis of foreign studies is carried out, since in the domestic literature there are no proven schemes for numerically assessing the effect of congestion of trees in front of the bridge on increasing the level of water in passing floods. It is shown that for the formation of congestion of trees, the greatest danger is the presence in the stream of Large woody debris – trees with a developed crown and root system. Linear objects – floating logs, even with their considerable size, pose significantly less danger due to the features of the hydrodynamics of channel flows. The proofs are carried out theoretically based on the generally accepted equations of hydraulics. Relationships are proposed for assessing a possible increase in water level during the formation of congestion of trees in front of the bridge. The results of numerical calculations are presented in the form of corresponding calculation graphs, since the developed relations do not have analytical solutions. Recommendations are given on reducing both the risks of formation of congestion of trees in front of the bridge and their negative consequences. It is shown that this task is not only hydrological, technical, but also, first, economic. Therefore, in each case, it is necessary to consider specially a set of measures to minimize the risks associated with the formation of congestion of trees in front of the bridge. The range of measures can be very wide: from stripping of coastal strips to the engineering and technical preparation of the territory, primarily within the boundaries of settlements, to the passage of floods with an increased level of flooding.